Predicting conifer establishment post wildfire in mixed conifer forests of the North American Mediterranean‐climate zone - Welch, Kevin R.; Safford, Hugh D.; Young, Truman P. (Ecosphere (Washington, D.C), 2016)
Due to fire suppression policies, timber harvest, and other management practices over the last century, many low‐ to mid‐elevation forests in semiarid parts of the western United States have accumulated high fuel loads and dense, multi‐layered canopies that are dominated by shade‐tolerant and fire‐sensitive conifers. To a great extent, the future status of western US forests will depend on tree species’ responses to patterns and trends in fire activity and fire behavior and postfire management decisions. This is especially the case in the North American Mediterranean‐climate zone ( NAMCZ ), which supports the highest precipitation variability in North America and a 4‐ to 6‐month annual drought, and has seen greater‐than‐average increases in air temperature and fire activity over the last three decades. We established 1490 survey plots in 14 burned areas on 10 National Forests across a range of elevations, forest types, and fire severities in the central and northern NAMCZ to provide insight into factors that promote natural tree regeneration after wildfires and the differences in postfire responses of the most common conifer species. We measured site characteristics, seedling densities, woody shrub, and tree growth. We specified a zero‐inflated negative binomial mixed model with random effects to understand the importance of each measured variable in predicting conifer regeneration. Across all fires, 43% of all plots had no conifer regeneration. Ten of the 14 fires had median conifer seedling densities that did not meet Forest Service stocking density thresholds for mixed conifer forests. When regeneration did occur, it was dominated by shade‐tolerant but fire‐sensitive firs ( Abies spp.), Douglas‐fir ( Pseudotsuga menziesii ) and incense cedar ( Calocedrus decurrens ). Seedling densities of conifer species were lowest in sites that burned at high severity, principally due to the biotic consequences of high severity fire, for example, increased distances to live seed trees and competition with fire‐following shrubs. We developed a second model specifically for forest managers and restoration practitioners who work in yellow pine and mixed conifer forests in the central NAMCZ to assess potential natural regeneration in the years immediately following a fire, allowing them to prioritize which areas may need active postfire forest restoration and supplemental planting.